Beyond Tradition: Muhammad Arkoun’s Multidisciplinary Approach to Qur'anic Interpretation - Ulumudin, Ihya' (Moderasi : Journal of Islamic Studies, 2024)
This study explores Muhammad Arkoun’s hermeneutical approach to Qur'anic interpretation, which emphasizes the importance of understanding the Qur'an within its socio-historical context. Arkoun’s critical stance toward traditional Islamic scholarship and his advocacy for a multidisciplinary framework have made significant contributions to modern Qur'anic studies. The study aims to analyze Arkoun’s method, focusing on his use of historical, anthropological, and semiotic-linguistic approaches to reinterpret revelation in a contemporary context. The qualitative methodology employed in this study involves an extensive literature review and contextual analysis of Arkoun’s works, examining his key concepts such as wahyu (revelation), Umm al-Kitab (Mother of the Book), and liqa’ Allah (meeting with God). The findings reveal that Arkoun challenges the static understanding of the Qur'an by promoting a dynamic and adaptable interpretation that responds to modern societal needs. His emphasis on historical contextualization allows for a nuanced understanding of the Qur'an’s ethical and social principles, particularly in addressing issues such as gender equality, human rights, and interfaith dialogue. Arkoun’s semiotic-linguistic approach provides further depth to his analysis by uncovering the symbolic and rhetorical structures within the Qur'an. However, his methodology also faces criticism, particularly from scholars concerned about the potential erosion of the Qur'an’s sacredness and the risk of subjective interpretation. The study concludes that Arkoun’s hermeneutical framework offers a valuable contribution to contemporary Islamic thought by encouraging critical engagement with the Qur'an in ways that promote inclusivity, adaptability, and dialogue between tradition and modernity. His approach underscores the necessity of continuous reinterpretation to keep the Qur'an relevant to evolving ethical, social, and political challenges. The findings suggest that further research could explore the practical applications of Arkoun’s hermeneutics in various contemporary contexts, contributing to the ongoing evolution of Qur'anic interpretation and Islamic studies. Keywords: Muhammad Arkoun, Hermeneutics, Qur'anic Interpretation, Historical Contextualization, Semiotic Analysis, Islamic Thought